2016
DOI: 10.1016/j.ijscr.2016.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Late reconstruction of the patellar tendon in rheumatoid arthritis using bone-patellar tendon-bone allograft

Abstract: HighlightsA lady with rheumatoid arthritis had a chronic patellar tendon rupture.She underwent patellar tendon reconstruction with a massive BTB allograft.She now has an active range of motion between −20 and 120°.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Forty-eight studies were sent for data extraction after the screening process (Fig 1). Two studies were excluded because of insufficient reporting of patient demographics and outcomes, 18,33 two studies were excluded due to inadequate follow-up, 6,16 and 35 studies were excluded due to being level V evidence, 4,5,7,[9][10][11][12][13]15,[17][18][19][20]22,24,25,[27][28][29][30][31][33][34][35][36][37][38][39][40][41][42]44,[46][47][48][49][50] leaving 9 studies for inclusion in our review. 3,8,14,21,23,26,32,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Forty-eight studies were sent for data extraction after the screening process (Fig 1). Two studies were excluded because of insufficient reporting of patient demographics and outcomes, 18,33 two studies were excluded due to inadequate follow-up, 6,16 and 35 studies were excluded due to being level V evidence, 4,5,7,[9][10][11][12][13]15,[17][18][19][20]22,24,25,[27][28][29][30][31][33][34][35][36][37][38][39][40][41][42]44,[46][47][48][49][50] leaving 9 studies for inclusion in our review. 3,8,14,21,23,26,32,…”
Section: Resultsmentioning
confidence: 99%
“…Forty-eight studies were sent for data extraction after the screening process ( Fig 1 ). 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 Two studies were excluded because of insufficient reporting of patient demographics and outcomes, 18 , 33 two studies were excluded due to inadequate follow-up, 6 , 16 and 35 studies were excluded due to being level V evidence, 4 , 5 , 7 , 9 , 10 , 11 , 12 , 13 , 15 , 17 , 18 , 19 , 20 , 22 , 24 , ...…”
Section: Resultsmentioning
confidence: 99%
“…Temponi et al [ 25 ] reported a good surgical outcome by using contralateral BPTB autograft in chronic patellar tendon rupture. And reconstruction using BPTB allograft in patients with rheumatoid arthritis was introduced [ 20 ]. However, existing methods to affix the bone block cannot be free from the disadvantages of having patellar fracture and wide anterior knee involvement such as osteotomy of the patella [ 17 , 26 ].…”
Section: Discussion and Findingsmentioning
confidence: 99%